Budget impact analysis of the fentanyl buccal tablet for treatment of breakthrough cancer pain - Darbà J; Kaskens L; Sánchez-de la Rosa R (Dove Medical Press, 2013)
Josep Darbà,1 Lisette Kaskens,2 Rainel Sánchez-de la Rosa31University of Barcelona, Barcelona, 2BCN Health Economics and Outcomes Research SL, Barcelona, 3Medical and HEOR Department, TEVA Pharmaceutical Industries Ltd, Madrid, SpainBackground: The purpose of this study was to assess the economic impact of the fentanyl buccal tablet for the management of breakthrough cancer pain (BTcP) in Spain.Methods: A 4-year budget impact model was developed for the period 2012–2015 for patients with BTcP from the perspective of the Spanish National Health System. BTcP products included in this model were rapid-onset opioids containing fentanyl (buccal, sublingual, or nasal transmucosal). Prevalence data on cancer, BTcP, opioid use, and number of BTcP episodes were obtained from the literature. Input data on health care resources associated with opioid use and opioid-induced side effects were obtained by consulting experts in oncology from different Spanish hospitals. Resources used included drugs, medical and emergency visits, other nonpharmacologic treatments, and treatment of opioid-induced side effects. Unit costs were obtained from the literature, and a 3% discount rate was applied to costs. Based on the unit costs for drugs and health care resources, the annual BTcP treatment costs per patient associated with each fentanyl product were determined to estimate the overall budget impact based on the total treatment population and the percentage of drug utilization associated with each product. One-way sensitivity analyses were conducted to test the robustness of the model.Results: Patients treated with oral opioids for BTcP were estimated at 23,291 in 2012, with an increase up to 23,413 in 2015. The average annual budget savings, with an increase of fentanyl buccal tablets, fentanyl sublingual tablets, and intranasal fentanyl spray, and a decrease in oral transmucosal fentanyl citrate, was estimated at €2.6 million, which represents a 0.5% decrease in the total costs of BTcP over the next 4 years. Results of the sensitivity analysis showed that the model was most sensitive to drug cost per day for the fentanyl buccal tablet. A 50% decrease in the daily cost of the fentanyl buccal tablet resulted in the largest overall decrease in budget impact of €5.4 million.Conclusion: The increase in use of the fentanyl buccal tablet leads to overall savings in the budget impact for the Spanish National Health System. Although the economic impact of treatment for BTcP was shown to increase over 4 years due to population growth, the average annual cost per patient was reduced by €29 with increased use of the fentanyl buccal tablet.Keywords: cancer, breakthrough pain, economic analysis, costs, rapid onset opioids